Enhancement of DNA immunization against hepatitis B following coexpression of costimulatory molecules. - Balasubramanian, Sowmya. (University of Ottawa (Canada), 2000)
The use of plasmid DNA encoding antigens has given rise to a novel class of vaccines, that may overcome many of the disadvantages associated with classical antigen-based vaccines. This thesis examines specific methods of optimizing immune responses directed against the hepatitis B virus surface antigen (HBsAg) encoded by a plasmid expression system in BALB/c mice. Interaction of B7.1 and B7.2 with their receptor CD28/CTLA-4 molecules on T cells is known to facilitate progression of the T cell through the cycle of immune activation. We have determined whether coexpression of costimulatory molecules, B7.1 or B7.2, along with HBsAg from a DNA vaccine, administered as separate plasmids (codelivery) or encoded within the same expression vector (colinear expression), can augment HBsAg-specific humoral and cell-mediated responses. Intramuscular (IM) coexpression of B7.1 or B7.2 along with the DNA vaccine significantly enhanced cytotoxic T lymphocyte (CTL) responses whereas coexpression of B7.2 alone enhanced CTL responses with intradermal (ID) administration. However, there was no concomitant increase in humoral responses with coexpression by either route of administration. In contrast colinear expression of B7.1 or B7.2 significantly enhanced humoral as well as CTL responses with both IM and ID routes of administration. Furthermore, the Th2 bias that is seen with ID administration is skewed towards a Th1 response with B7 coexpression. The kinetics of plasmid DNA distribution in various anatomical compartments were also studied in order to address the differences in immune responses noted with IM and ID routes of administration. Collectively the results suggest that B7 coexpression can augment or alter responses to DNA vaccines and might prove effective for immunization in humans.
Keywords: Biology, Molecular.